The Effect of Mobile Learning Integrated Traditional Games Egrang to Improve Multiple Representation Skills - Anggi Datiatur Rahmat; Insih Wilujeng; Heru Kuswanto (Journal of Science Learning, 2023)
Integrating traditional games into science learning can reconstruct local knowledge into scientific knowledge. One of the most popular technologies today is the mobile phone, which almost everyone uses. This study investigates the effect of mobile learning integrated with traditional games Egrang on students' multiple representation skills. This study used a quasi-experimental design of 64 7th junior high school students randomly assigned to experimental and control groups who learn motion and force concepts. Learning activities in the experimental class used mobile learning, while the control class used textbooks. The experimental class with (t = 8.78, p .05) and N-gain score 0.20. Besides, the control class with (t = 3.87, p .05) and N-gain score of 0.09. The study results found that students in the experimental class scored more in multiple representation skills than in the control class. Mobile learning integrated traditional games Egrang improves students' multiple representation skills, especially pictorial and mathematical representation. The results of this study can be used as a reference for integrating technology and indigenous knowledge into another science concept.